EXPLORING LEGITIMATE PERIPHERAL PARTICIPATION OF STUDENTS IN A COLLEGE MATHEMATICS COURSE - Avelino G. Ignacio Jr. (International Journal of Education, 2022)
Students, by just listening to and being observant of mathematical procedures to gain conceptual knowledge in mathematics, do not often lead valuable performance. Students need to participate. Learning is initiated and enhanced via continuing legitimate participation in a community of practice. Hence, this study explores students' legitimate peripheral participation in a college mathematics course, explicitly to describe the (1) activities students do to refine practice, (2) barriers students face to advance to full participation, and (3) participation support structures that allow students' legitimate peripheral participation. This study used qualitative-exploratory research design via the qualitative tool—reflective journal—comprising second-year teacher education students (N = 42) from a state university in Bulacan, Philippines, taking the Logic and Set Theory course as study participants, obtained purposively. Data were analyzed through thematic coding. This study showed that the activities of students that refine their practice could be thematized as individual engagement or collaborative involvement. Students faced both intrinsic and extrinsic barriers in progressing to full participation. The participation support structures facilitating students' legitimate peripheral participation were the manifestation of a welcoming environment that offered students additional practice activities to work into supplemented with constructive feedback, joined with the convenience of peer groups where they could go when needed. Inspirational life quotes, fascinating lessons that stir interest, and closed knowledge gaps equally enable student participation. A legitimate peripheral participation activity cycle may still arise when faced with difficulties as participants gradually try to work independently. A friendship-based collaborative group is suggested for Filipino learners.